Graduate Studies Schooling during COVID-19 Pandemic: Doctorate and Master’s Students Experience in a Private Higher Education Institution in the Philippines - Osea, Eleanor Albia (IJBLE Scientific Publications Community Inc., 2022)
This study determined the graduate schooling experiences of the 347 Graduate Students of the University of Northeastern Philippines, Iriga City, Philippines, during the Second Semester of the Academic Year 2020-2021, wherein online learning modality instead of traditional face-to-face classes was implemented. Using a survey questionnaire distributed through Google form, it sought answers to the learning experiences of the Graduate Students with regards to their graduate schooling during the COVID-19 pandemic and their challenges met achieving quality graduate programs during the New Normal School Year. Descriptive survey research was used. All respondents strongly agreed that a sudden transition to a different modality in Graduate School teaching affects the quality of professional learning experiences, and they faced challenges that affect their graduate learning experiences